A polyionic liquid electrolyte for lithium-sulfur battery and its preparation method and application
By using polyion liquid electrolyte composed of polyion liquid, lithium salt and pyrrolidine ion liquid, the problems of flammable and explosive lithium-sulfur battery electrolyte and low ion conductivity of solid sulfide electrolyte are solved, and the stability and safety of high-temperature cycles are improved.
Patent Information
- Application Number
- CN202210711572.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-06-22
AI Technical Summary
The electrolytes of existing lithium-sulfur batteries are at risk of flammability and explosion, and the solid sulfide electrolyte has low room temperature ionic conductivity, poor interface contact, and harsh preparation conditions.
A polyion liquid electrolyte composed of polyion liquid, lithium salt and pyrrolidine ion liquid is used. The electrolyte is obtained by in-situ polymerization and has high chemical stability and can form a stable solid electrolyte interface layer with the lithium metal negative electrode to prevent further consumption of the lithium metal negative electrode and the pyrrolidine ion liquid.
It improves the cycle stability of lithium-sulfur batteries at high temperatures, inhibits the shuttle effect of polysulfides, has flame retardant properties, and improves the safety of the batteries.
Smart Images

Figure CN114976234B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of gel electrolytes, and in particular, relates to a polyionic liquid electrolyte for lithium-sulfur batteries and a preparation method and application thereof. Background Art
[0002] With the extensive application of consumer electronics, power batteries and energy storage scenarios, people's demand for high energy density lithium-ion batteries is increasing. Lithium metal anode has a high theoretical capacity (3860mAh g -1 ), low operating voltage (-3.045V), and is regarded as an ideal material for the negative electrode of lithium-ion batteries. However, lithium metal is too active and has problems such as continuous reaction with the electrolyte, lithium dendrite growth and safety. The electrolytes currently used in lithium-sulfur batteries are mainly carbonate (EC / DMC / FEC) and ether (DOL / DME) electrolytes, both of which are flammable and explosive. Although the room temperature ionic conductivity of solid sulfide electrolytes suitable for lithium-sulfur batteries can reach the order of millisiemens per centimeter, the solid-solid contact between the electrodes is poor, the battery assembly process is complex and needs to operate under high external pressure, and it needs to be strictly anhydrous and oxygen-free, and the preparation conditions are harsh. As a quasi-solid-state battery system, gel electrolyte can have both good interface contact and high ionic conductivity, and has great application prospects.
[0003] In the present invention, the polyionic liquid electrolyte has good stability with the lithium metal negative electrode and the sulfur positive electrode. Compared with the traditional carbonate electrolyte, the lithium-sulfur battery assembled with the polyionic liquid electrolyte has not only a high specific capacity but also good cycle stability when working at high temperature (50-100°C). Summary of the invention
[0004] In view of the defects in the prior art, the present invention uses a polyionic liquid electrolyte composed of a polyionic liquid, a lithium salt and a pyrrolidine ionic liquid. The polyionic liquid electrolyte has high chemical stability and can form a stable solid electrolyte interface layer with the lithium metal negative electrode to prevent further consumption of the lithium metal negative electrode and the pyrrolidine ionic liquid, and is expected to improve the cycle stability of the lithium-sulfur battery at high temperature. Since polysulfides cannot be dissolved in pyrrolidine ionic liquids, the use of polyionic liquid electrolytes can effectively inhibit the shuttle effect of polysulfides. At the same time, the polyionic liquid electrolyte has flame retardant properties and can effectively improve the safety of lithium-sulfur batteries.
[0005] The purpose of the present invention is to provide a polyionic liquid electrolyte for lithium-sulfur batteries, a preparation method and applications of high-temperature lithium-sulfur batteries.
[0006] The object of the present invention is achieved through the following solutions:
[0007] In a first aspect, the present invention provides a polyionic liquid electrolyte for a lithium-sulfur battery, wherein the polyionic liquid electrolyte for a lithium-sulfur battery is obtained by heating a polyionic liquid precursor solution and then subjecting it to in-situ polymerization; the polyionic liquid precursor solution comprises a pyrrolidine ionic liquid, a thermal initiator, a polyionic liquid precursor monomer and a lithium salt.
[0008] As an embodiment of the present invention, the structural formula of the polyionic liquid precursor monomer is as follows:
[0009]
[0010] Wherein, X is one of a bis(trifluoromethylsulfonyl)imide anion and a bis(fluoromethylsulfonyl)imide anion.
[0011] As an embodiment of the present invention, the thermal initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile and benzoyl peroxide.
[0012] As an embodiment of the present invention, the pyrrolidine ionic liquid has the structural formula:
[0013]
[0014] Wherein, m is an integer of 1 to 2, and X is one of bistrifluoromethylsulfonyl imide anion and bisfluoromethylsulfonyl imide anion. The pyrrolidine ionic liquid selected in the present invention can inhibit the shuttling of polysulfides, and compared with commercial lithium-sulfur electrolytes such as carbonate electrolytes and ether electrolytes, it has flame retardant properties, and gives lithium-sulfur batteries high safety.
[0015] As an embodiment of the present invention, the lithium salt is one or more of lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl imide), and lithium bis(fluoromethylsulfonyl imide). The concentration of the lithium salt is 1 to 4 mmol / g. The present invention dissolves the lithium salt in a pyrrolidine ionic liquid and dopes it in a polyionic liquid electrolyte as a carrier conducting ion.
[0016] As an embodiment of the present invention, the ratio of the polyionic liquid precursor monomer, thermal initiator, lithium salt and pyrrolidine ionic liquid is 0.25-0.67g: 0.00625-0.00835g: 1-4mmol: 1g. The mass ratio of the polyionic liquid precursor monomer and the pyrrolidine ionic liquid is preferably one of 2:8, 3:7 and 4:6.
[0017] As an embodiment of the present invention, the heating temperature is 30 to 90° C. and the heating time is 5 to 600 minutes. In the present invention, methacryloyloxyethyl trimethyl ammonium chloride can be used to obtain a polyionic liquid precursor monomer with different anions through ion exchange. After heating to initiate a polymerization reaction, a polyionic liquid is obtained, and the polyionic liquid is mixed with a pyrrolidine ionic liquid and a lithium salt in a certain proportion to obtain a highly elastic polyionic liquid electrolyte.
[0018] As an embodiment of the present invention, the preparation method of the polyionic liquid precursor monomer is as follows: dissolving methacryloyloxyethyl trimethyl ammonium chloride and lithium salt in water, stirring and reacting, washing, and freeze-drying to obtain the polyionic liquid precursor monomer. The stirring reaction is carried out at room temperature, and the washing is to wash the oil phase with water 2-5 times. Methacryloyloxyethyl trimethyl ammonium chloride can be used to obtain a polyionic liquid precursor monomer with different anions through ion exchange.
[0019] The structural formula of the methacryloyloxyethyl trimethylammonium chloride is:
[0020]
[0021] In the method for preparing a polyionic liquid precursor monomer, the lithium salt includes one of lithium bis(trifluoromethylsulfonyl)imide and lithium bis(fluoromethylsulfonyl)imide. The molar ratio of methacryloyloxyethyltrimethylammonium chloride, lithium salt and water is 1:1.05:0.55.
[0022] In a second aspect, the present invention provides a method for preparing a polyionic liquid electrolyte for a lithium-sulfur battery, the preparation method comprising the following steps:
[0023] A1, dissolving a polyionic liquid precursor monomer, a thermal initiator and a lithium salt in a pyrrolidine ionic liquid, and stirring to obtain a polyionic liquid precursor solution;
[0024] A2. Under the protection of an inert atmosphere, the polyionic liquid precursor solution is heated to initiate an in-situ polymerization reaction of the polyionic liquid precursor monomer to obtain the polyionic liquid electrolyte for the lithium-sulfur battery.
[0025] As an embodiment of the present invention, the heating temperature in step A2 is 30 to 90° C., and the heating time is 5 to 600 minutes.
[0026] As an embodiment of the present invention, the structural formula of the polyionic liquid obtained by the polymerization reaction in step A2 is:
[0027]
[0028] Wherein, n is an integer of 2 to 1000, X is one of bistrifluoromethylsulfonyl imide anion and bisfluoromethylsulfonyl imide anion. The polymerization degree of the polyionic liquid is 2 to 1000.
[0029] The present invention also provides a method for preparing a polyionic liquid, the preparation method comprising the following steps:
[0030] (1) dissolving methacryloyloxyethyl trimethylammonium chloride and lithium salt in water, stirring and reacting at room temperature, washing the oil phase three times with water, and freeze-drying to obtain a polyionic liquid precursor monomer; the lithium salt comprises one of bistrifluoromethylsulfonyl imide lithium and bisfluoromethylsulfonyl imide lithium;
[0031] (2) adding the polyionic liquid precursor monomer and thermal initiator obtained in step (1) into an organic solvent, stirring for reaction, and heating under the protection of an inert atmosphere to initiate a free radical polymerization reaction to obtain a polyionic liquid solution;
[0032] (3) dropping the polyionic liquid solution obtained in step (2) into a precipitant for precipitation, and then vacuum filtering and drying to obtain a polyionic liquid.
[0033] The organic solvent in step (2) includes one or more of dioxane, N,N-dimethylformamide, and tetrahydrofuran. The precipitant is one or more of diethyl ether, n-heptane, and n-hexane.
[0034] In a third aspect, the present invention provides a lithium-sulfur battery comprising the above-mentioned polyionic liquid electrolyte.
[0035] In a fourth aspect, the present invention provides a method for preparing a lithium-sulfur battery, the preparation method comprising the following steps: dissolving a polyionic liquid precursor monomer, a thermal initiator and a lithium salt in a pyrrolidine ionic liquid, dropping the polyionic liquid precursor solution onto a diaphragm, assembling a lithium-sulfur battery with a sulfur positive electrode and a lithium metal negative electrode on both sides, inducing an in-situ polymerization reaction by heating, and obtaining a lithium-sulfur battery containing a polyionic liquid electrolyte.
[0036] The present invention drips a polyionic liquid precursor solution onto a diaphragm and initiates an in-situ polymerization reaction by heating. In the polyionic liquid electrolyte, there is an ionic bond between the polyionic liquid and the pyrrolidine ionic liquid, so that the viscoelasticity of the polyionic liquid electrolyte can be controlled. When more pyrrolidine ionic liquid is added, it gradually becomes an ionic liquid electrolyte; when more polyionic liquid is added, it becomes harder and more brittle. The pyrrolidine ionic liquid plays a role in conducting lithium ions and inhibiting the shuttling of lithium polysulfide. These two structures work together to enable the polyionic liquid electrolyte to adapt to the volume effect of the sulfur positive electrode during charging and discharging and have good ionic conductivity. The interface impedance between the polyionic liquid electrolyte obtained by in-situ polymerization and the electrode is small, which is conducive to the conduction of lithium ions. At the same time, compared with carbonate electrolytes, lithium-sulfur batteries assembled with the polyionic liquid electrolyte can effectively improve high-temperature cycle stability.
[0037] As an embodiment of the present invention, the preparation method specifically comprises the following steps:
[0038] S1, dissolving a polyionic liquid precursor monomer, a thermal initiator and a lithium salt in a pyrrolidine ionic liquid to obtain a polyionic liquid precursor solution;
[0039] S2, dripping the polyionic liquid precursor solution onto the diaphragm, and assembling the lithium-sulfur battery with sulfur positive electrode and lithium metal negative electrode on both sides;
[0040] S3, heating the lithium-sulfur battery obtained in step S2 to obtain a lithium-sulfur battery containing a polyionic liquid electrolyte.
[0041] As an embodiment of the present invention, the thickness of the lithium metal negative electrode in step S2 is 100 to 400 microns; the sulfur positive electrode is one of sulfurized polyacrylonitrile and sulfur-selenized polyacrylonitrile.
[0042] As an embodiment of the present invention, the heating temperature in step S3 is 30 to 90 degrees, and the heating time is 5 to 600 minutes.
[0043] As an embodiment of the present invention, the operating temperature range of the lithium-sulfur battery is 25° C.-100° C. The polyionic liquid electrolyte of the present invention has good cycle stability and flame retardant properties at high temperatures, which is different from commercial lithium-sulfur battery electrolytes.
[0044] The polyionic liquid precursor monomer, thermal initiator and lithium salt are dissolved in the pyrrolidine ionic liquid, the solution is dripped on the diaphragm, sulfur is used as the positive electrode and lithium foil is used as the negative electrode, and a button battery is assembled. After standing for a period of time, the lithium-sulfur battery is placed in a constant temperature oven for constant temperature heating to initiate the in-situ polymerization reaction of the polyionic liquid precursor monomer. The pyrrolidine ionic liquid is used to dissolve the lithium salt and conduct lithium ions, and the polyionic liquid can react with the lithium metal negative electrode and the sulfur positive electrode to form a stable solid electrolyte interface layer; the polyionic liquid and the ionic liquid form an elastomer with adjustable strength through ionic bonds to adapt to the volume change of the sulfur positive electrode. Through the technical solution designed by the present invention, the two specific structures in the polyionic liquid electrolyte play a role at the same time, so that the electrolyte can not only ensure high ionic conductivity and flame retardant properties, but also effectively overcome the volume change of the sulfur positive electrode and the dissolution shuttle of polysulfides, thereby preparing a high-safety high-temperature lithium-sulfur battery.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The present invention provides a simple method for preparing a polyionic liquid precursor monomer. Since the distribution coefficient of lithium chloride in the aqueous phase is larger after ion exchange, the purification purpose can be achieved by multiple water washings. At the same time, since the polyionic liquid precursor monomer is immiscible with water after ion exchange, it is easy to separate, and trace amounts of water can be removed by freeze drying.
[0047] (2) The present invention provides a method for assembling a lithium-sulfur battery by in-situ polymerization, wherein a polyionic liquid precursor solution is dripped onto a diaphragm, and a sulfur positive electrode and a lithium metal negative electrode are assembled on both sides to form a lithium-sulfur battery. The in-situ polymerization reaction is initiated by heating, thereby reducing the interface impedance between the electrode and the electrolyte;
[0048] (3) The polyionic liquid electrolyte prepared by the present invention has the characteristics of adjustable components and elasticity. Due to the existence of ionic bonds between the polyionic liquid and the pyrrolidine ionic liquid, the elasticity of the polyionic liquid electrolyte is adjustable, and the pyrrolidine ionic liquid can conduct lithium ions. These two structures work together to enable the polyionic liquid electrolyte to have good ionic conductivity and adapt to the volume change of the sulfur positive electrode, thereby improving the cycle stability of the lithium-sulfur battery. In addition, the flame retardant properties of the polyionic liquid electrolyte can improve the safety performance of the lithium-sulfur battery;
[0049] (4) The polyionic liquid electrolyte prepared by the present invention can inhibit the dissolution of lithium polysulfide generated during the charge and discharge process of the sulfur positive electrode, thereby maintaining the high specific capacity of the lithium-sulfur battery during the charge and discharge cycle. After disassembling the lithium-sulfur battery, it was found that the diaphragm was colorless and translucent, and no yellow lithium polysulfide was found to be dissolved;
[0050] (5) The polyionic liquid electrolyte prepared by the present invention is stable to the lithium metal negative electrode. A lithium-lithium symmetrical battery was assembled using the polyionic liquid electrolyte and a lithium deposition-dissolution test was performed. The symmetrical battery can still remain stable for a long time. After disassembling the symmetrical battery, it was found that a dense solid electrolyte interface layer was formed on the surface of the lithium metal;
[0051] (6) Compared with pure ionic liquid electrolyte, the addition of polyionic liquid can form an elastic solid electrolyte interface layer on the electrode surface that can conduct ions, preventing the continuous reaction and consumption of pyrrolidine ionic liquid and lithium metal negative electrode;
[0052] (7) The polyionic liquid electrolyte prepared by the present invention is more stable at high temperatures than the carbonate electrolyte. When the temperature exceeds 50°C, the violent side reaction between the carbonate electrolyte and the metal lithium negative electrode accelerates the attenuation of the lithium-sulfur battery, while the polyionic liquid electrolyte can still work stably at 50°C or even 100°C, which makes it possible for lithium-sulfur batteries to work in high temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0054] Figure 1 is a schematic diagram of the synthesis of the polyionic liquid precursor monomer in Example 1;
[0055] Figure 2 is a schematic diagram of in-situ polymerization of the polyionic liquid precursor solution in Example 1;
[0056] Figure 3 The figure is a comparison of the charge and discharge cycle test of a lithium-sulfur battery assembled with carbonate electrolyte (liquid, electrolyte, LE) (Comparative Example 1) and a lithium-sulfur battery assembled with polyionic liquid electrolyte (polyionic liquid electrolyte, PIL) (Example 1) at 50 degrees Celsius and 0.2C rate (sulfurized polyacrylonitrile: 1C = 1675mA g -1 );
[0057] Figure 4 The lithium deposition-dissolution test of the lithium-lithium symmetric battery assembled with the polyionic liquid electrolyte at 0.5 mA and 50 degrees Celsius in Example 9;
[0058] Figure 5 Schematic diagram of the stretching of the polyionic liquid electrolyte in Example 10. DETAILED DESCRIPTION
[0059] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0060] The following are comparative examples and embodiments:
[0061] Comparative Example 1
[0062] The carbonate electrolyte (1M LiPF6:EC / DMC / FEC) was dripped onto the Celgard diaphragm to completely wet it after absorbing the liquid. The sulfide polyacrylonitrile positive electrode, Celgard diaphragm containing carbonate electrolyte, lithium foil, steel sheet, and shrapnel were stacked on the 2032 button battery positive electrode shell in sequence, and finally the 2032 button battery negative electrode shell was covered. The sealer was pressurized and sealed, and the shell was left in the glove box for 12 hours to ensure that the electrolyte was completely infiltrated. The button battery was charged and discharged at a rate of 0.2C at 50 degrees Celsius. After 22 cycles, the discharge capacity was about 738mAh g -1 , the capacity retention rate is 59.3%.
[0063] Comparative Example 2
[0064] This comparative example provides a lithium-sulfur battery, and its preparation method is basically the same as that of Example 1, except that the piperidine ionic liquid is 1-methyl-1-propylpiperidinylfluoromethylsulfonyl imide.
[0065] The lithium-sulfur battery was charged and discharged at a rate of 0.2C. After 200 cycles, the coulombic efficiency was about 46% and the discharge capacity remained at 782.3 mAh g -1 , the capacity retention rate is less than 56%.
[0066] Example 1
[0067] The preparation method is as follows: 18.7 g of lithium bis(fluoromethanesulfonyl)imide and 26 g of methacryloyloxyethyl trimethylammonium chloride are dissolved in 10 mL of deionized water, stirred with a magnetic stirrer for 10 minutes, the upper aqueous solution is removed, and 10 mL of deionized water is added to wash the lower organic phase, and the process is repeated three times. After being frozen into a solid with liquid nitrogen, the trace amount of water is removed by freeze drying to obtain a polyionic liquid precursor monomer [MATAC] [FSI], which is synthesized as follows: Figure 1 shown.
[0068] 0.8 g of polyionic liquid precursor monomer [MATAC][FSI], 0.374 g of lithium bis(fluoromethanesulfonyl)imide and 40 mg of azobis(isobutyronitrile) were dissolved in 1.2 g of 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide (Py13 FSI) and stirred at room temperature for 1 hour. Figure 2 As shown, the solution is dripped onto the glass fiber diaphragm, and the sulfide polyacrylonitrile positive electrode, glass fiber diaphragm, lithium foil, steel sheet, and shrapnel are stacked on the 2032 button battery positive electrode shell in sequence, and finally covered with the 2032 battery negative electrode shell. The sealing machine is pressurized to seal and allowed to stand in the glove box for 12 hours to ensure that the ionic liquid solution infiltrates the electrode surface. After taking out the button battery, put it in an oven and heat it at 90 degrees Celsius for 5 minutes. After heating, the charge and discharge cycle test is carried out at 50 degrees Celsius. Figure 3 As shown in the figure, the lithium-sulfur battery was charged and discharged at a rate of 0.2C. After 200 cycles, the coulombic efficiency was greater than 99.5%, and the discharge capacity remained at 1050 mAh g -1 The capacity retention rate is greater than 99% (calculated based on 10 cycles of charge and discharge activation).
[0069] Example 2
[0070] The preparation method is as follows: 18.7 g of lithium bis(fluoromethanesulfonyl)imide and 26 g of methacryloyloxyethyl trimethylammonium chloride are dissolved in 10 mL of deionized water, stirred with a magnetic stirrer for 10 minutes, the upper aqueous solution is removed, and 10 mL of deionized water is added to wash the lower organic phase, and the process is repeated three times. After being frozen into a solid with liquid nitrogen, the trace amount of water is removed by freeze drying to obtain a polyionic liquid precursor monomer [MATAC] [FSI].
[0071] 0.4 g of polyionic liquid precursor monomer [MATAC][FSI], 0.374 g of lithium bis(fluoromethanesulfonyl)imide and 10 mg of azobis(isoheptyl)nitrile were dissolved in 1.6 g of 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide (Py 13 FSI) and stirred at room temperature for 1 hour. The solution was dripped onto the glass fiber diaphragm, and the sulfide polyacrylonitrile positive electrode, glass fiber diaphragm, lithium foil, steel sheet, and shrapnel were stacked on the 2032 button battery positive electrode shell in sequence, and finally covered with the 2032 button battery negative electrode shell. The sealing machine was pressurized and sealed, and the battery was allowed to stand in the glove box for 12 hours to ensure that the ionic liquid solution infiltrated the electrode surface. After taking out the button battery, it was placed in an oven and heated at 70 degrees Celsius for 12 hours. After heating, a charge and discharge cycle test was performed at 100 degrees Celsius. After 200 cycles, the capacity retention rate was greater than 99%, and the discharge specific capacity was approximately 1380mAh g -1 .
[0072] Example 3
[0073] The preparation method is as follows: 18.7 g of lithium bis(fluoromethanesulfonyl)imide and 26 g of methacryloyloxyethyl trimethylammonium chloride are dissolved in 10 mL of deionized water, stirred with a magnetic stirrer for 10 minutes, the upper aqueous solution is removed, and 10 mL of deionized water is added to wash the lower organic phase, and the process is repeated three times. After being frozen into a solid with liquid nitrogen, the trace amount of water is removed by freeze drying to obtain a polyionic liquid precursor monomer [MATAC] [FSI].
[0074] 0.4 g of polyionic liquid precursor monomer [MATAC][FSI], 0.374 g of lithium bis(fluoromethanesulfonyl)imide and 10 mg of benzoyl peroxide were dissolved in 1.6 g of 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide (Py 13 FSI) and stirred at room temperature for 1 hour. The solution was dripped onto the glass fiber diaphragm, and the sulfide polyacrylonitrile positive electrode, glass fiber diaphragm, lithium foil, steel sheet, and shrapnel were stacked on the 2032 button battery positive electrode shell in sequence, and finally covered with the 2032 button battery negative electrode shell. The sealing machine was pressurized and sealed, and the battery was allowed to stand in the glove box for 12 hours to ensure that the ionic liquid solution infiltrated the electrode surface. After taking out the button battery, it was placed in an oven and heated at 30 degrees Celsius for 12 hours. After heating, a charge and discharge cycle test was performed at 60 degrees Celsius. After 200 cycles, the capacity retention rate was greater than 99%, and the discharge specific capacity was approximately 1160mAh g -1 .
[0075] Example 4
[0076] The preparation method is as follows: 30.1 g of lithium bis(trifluoromethanesulfonyl)imide and 26 g of methacryloyloxyethyl trimethylammonium chloride are dissolved in 10 mL of deionized water, stirred with a magnetic stirrer for 10 minutes, the upper aqueous solution is removed, and 10 mL of deionized water is added to wash the lower organic phase, and the process is repeated three times. After being frozen into a solid with liquid nitrogen, trace water is removed by freeze drying to obtain a polyionic liquid precursor monomer [MATAC] [TFSI].
[0077] 0.8 g of polyionic liquid precursor monomer [MATAC][TFSI], 0.574 g of lithium bis(trifluoromethanesulfonyl)imide and 40 mg of azobis(isoheptyl)nitrile were dissolved in 1.2 g of 1-methyl-1-propylpyrrolidinium bis(trifluorosulfonyl)imide (Py 13 TFSI) and stirred at room temperature for 1 hour. The solution was dripped onto the glass fiber diaphragm, and the sulfur-selenide polyacrylonitrile positive electrode, glass fiber diaphragm, lithium foil, steel sheet, and shrapnel were stacked on the 2032 button battery positive electrode shell in sequence, and finally covered with the 2032 button battery negative electrode shell. The sealing machine was pressurized and sealed, and allowed to stand in the glove box for 12 hours to ensure that the ionic liquid solution infiltrated the electrode surface. After taking out the button battery, it was placed in an oven and heated at 90 degrees Celsius for 5 minutes. After heating, a charge and discharge cycle test was performed at 70 degrees Celsius. After 200 cycles, the capacity retention rate was about 78%, and the discharge specific capacity was about 680mAh g-1 .
[0078] Example 5
[0079] The preparation method is as follows: 18.7 g of lithium bis(fluoromethanesulfonyl)imide and 26 g of methacryloyloxyethyl trimethylammonium chloride are dissolved in 10 mL of deionized water, stirred with a magnetic stirrer for 10 minutes, the upper aqueous solution is removed, and 10 mL of deionized water is added to wash the lower organic phase, and the process is repeated three times. After being frozen into a solid with liquid nitrogen, the trace amount of water is removed by freeze drying to obtain a polyionic liquid precursor monomer [MATAC] [FSI].
[0080] 0.4 g of polyionic liquid precursor monomer [MATAC][FSI], 0.374 g of lithium bis(fluoromethanesulfonyl)imide and 10 mg of azobis(isobutyronitrile) were dissolved in 1.6 g of 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide (Py 13 FSI) and stirred at room temperature for 1 hour. The solution was dripped onto the glass fiber diaphragm, and the sulfide polyacrylonitrile positive electrode, glass fiber diaphragm, lithium foil, steel sheet, and shrapnel were stacked on the 2032 button battery positive electrode shell in sequence, and finally covered with the 2032 button battery negative electrode shell. The sealing machine was pressurized and sealed, and the battery was allowed to stand in the glove box for 12 hours to ensure that the ionic liquid solution infiltrated the electrode surface. After taking out the button battery, it was placed in an oven and heated at 70 degrees Celsius for 12 hours. After heating, a charge and discharge cycle test was performed at 70 degrees Celsius. After 200 cycles, the capacity retention rate was greater than 99%, and the discharge specific capacity was approximately 1220mAh g -1 .
[0081] Example 6
[0082] The preparation method is as follows: 18.7 g of lithium bis(fluoromethanesulfonyl)imide and 26 g of methacryloyloxyethyl trimethylammonium chloride are dissolved in 10 mL of deionized water, stirred with a magnetic stirrer for 10 minutes, the upper aqueous solution is removed, and 10 mL of deionized water is added to wash the lower organic phase, and the process is repeated three times. After being frozen into a solid with liquid nitrogen, the trace amount of water is removed by freeze drying to obtain a polyionic liquid precursor monomer [MATAC] [FSI].
[0083] 0.4 g of polyionic liquid precursor monomer [MATAC][FSI], 0.374 g of lithium bis(fluoromethanesulfonyl)imide and 10 mg of azobis(isobutyronitrile) were dissolved in 1.6 g of 1-methyl-1-butylpyrrolidinium bis(fluorosulfonyl)imide (Py 14FSI) and stirred at room temperature for 1 hour. The solution was dripped onto the glass fiber diaphragm, and the sulfide polyacrylonitrile positive electrode, glass fiber diaphragm, lithium foil, steel sheet, and shrapnel were stacked on the 2032 button battery positive electrode shell in sequence, and finally covered with the 2032 button battery negative electrode shell. The sealing machine was pressurized and sealed, and the battery was allowed to stand in the glove box for 12 hours to ensure that the ionic liquid solution infiltrated the electrode surface. After taking out the button battery, it was placed in an oven and heated at 70 degrees Celsius for 12 hours. After heating, a charge and discharge cycle test was performed at 70 degrees Celsius. After 200 cycles, the capacity retention rate was greater than 99%, and the discharge specific capacity was approximately 1380mAh g -1 .
[0084] Example 7
[0085] The preparation method of the gel polymer electrolyte is as follows: 18.7g of lithium bis(fluoromethanesulfonyl)imide and 26g of methacryloyloxyethyl trimethylammonium chloride are dissolved in 10mL of deionized water, stirred with a magnetic stirrer for 10 minutes, the upper aqueous solution is removed, and 10mL of deionized water is added to wash the lower organic phase, and the process is repeated three times. After being frozen into a solid by liquid nitrogen, trace water is removed by freeze drying to obtain a polyionic liquid precursor monomer [MATAC] [FSI].
[0086] 0.4 g of polyionic liquid precursor monomer [MATAC][FSI], 0.374 g of lithium bis(fluoromethanesulfonyl)imide and 10 mg of azobis(isobutyronitrile) were dissolved in 1.6 g of 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide (Py 13 FSI) and stirred at room temperature for 1 hour. The solution was dripped onto the glass fiber diaphragm, and the sulfide polyacrylonitrile positive electrode, glass fiber diaphragm, lithium foil, steel sheet, and shrapnel were stacked on the 2032 button battery positive electrode shell in sequence, and finally covered with the 2032 button battery negative electrode shell. The sealing machine was pressurized and sealed, and the battery was allowed to stand in the glove box for 12 hours to ensure that the ionic liquid solution infiltrated the electrode surface. After taking out the button battery, it was placed in an oven and heated at 70 degrees Celsius for 12 hours. After heating, a charge and discharge cycle test was performed at 40 degrees Celsius. After 200 cycles, the capacity retention rate was greater than 99%, and the discharge specific capacity was approximately 1110mAh g -1 .
[0087] Example 8
[0088] The preparation method of the gel polymer electrolyte is as follows: 18.7g of lithium bis(fluoromethanesulfonyl)imide and 26g of methacryloyloxyethyl trimethylammonium chloride are dissolved in 10mL of deionized water, stirred with a magnetic stirrer for 10 minutes, the upper aqueous solution is removed, and 10mL of deionized water is added to wash the lower organic phase, and the process is repeated three times. After being frozen into a solid by liquid nitrogen, trace water is removed by freeze drying to obtain a polyionic liquid precursor monomer [MATAC] [FSI].
[0089] 0.4 g of polyionic liquid precursor monomer [MATAC][FSI], 0.287 g of lithium difluorooxalatoborate and 10 mg of azobisisobutyronitrile were dissolved in 1.6 g of 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide (Py 13 FSI) and stirred at room temperature for 1 hour. The solution was dripped onto the glass fiber diaphragm, and the sulfur-selenide polyacrylonitrile positive electrode, glass fiber diaphragm, lithium foil, steel sheet, and shrapnel were stacked on the 2032 button battery positive electrode shell in sequence, and finally covered with the 2032 button battery negative electrode shell. The sealing machine was pressurized and sealed, and the battery was allowed to stand in the glove box for 12 hours to ensure that the ionic liquid solution infiltrated the electrode surface. After taking out the button battery, it was placed in an oven and heated at 70 degrees Celsius for 12 hours. After heating, a charge and discharge cycle test was performed at 30 degrees Celsius. After 200 cycles, the capacity retention rate was greater than 99%, and the discharge specific capacity was approximately 930mAh g -1 .
[0090] In order to simplify the description, the preparation parameters and charge-discharge cycle data of Examples 2 to 8 are listed in Table 1. The parameters not listed in the table are the same as those of Example 1.
[0091] Table 1 Preparation parameters and charge-discharge cycle data of Examples 1 to 8
[0092]
[0093] *Calculated based on 10 charge and discharge cycles
[0094] Lithium-sulfur battery data analysis
[0095] As the operating temperature of the lithium-sulfur battery increases, the discharge capacity of the lithium-sulfur battery gradually increases. As the ratio of the lithium-sulfur battery polyionic liquid precursor monomer to the pyrrolidine ionic liquid increases, the discharge capacity of the lithium-sulfur battery gradually decreases. Compared with the pyrrolidine ionic liquid 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide (Py 13 FSI), pyrrolidine ionic liquid 1-methyl-1-butylpyrrolidinium bis(fluorosulfonyl)imide (Py 14 FSI) has a higher discharge specific capacity, which may be due to the lithium ion in 1-methyl-1-butylpyrrolidinium bis(fluorosulfonyl)imide (Py 14 FSI) has stronger conductivity. Compared with the bis(trifluoromethylsulfonyl)imide anion system (TFSI - ), bis(fluoromethylsulfonyl)imide anion system (FSI - ) has better cycling stability, which may be due to the bis(fluoromethylsulfonyl)imide anion system (FSI - ) can form a more stable solid electrolyte interface layer with lithium metal. Compared with the sulfur selenide polyacrylonitrile positive electrode (Se 0.05 S0.95 PAN), sulfide polyacrylonitrile positive electrode (SPAN) has better cycle stability. The discharge capacity of lithium-sulfur batteries assembled with sulfide-selenide polyacrylonitrile positive electrode decays after cycling. Compared with polyionic liquid electrolytes, the discharge capacity of lithium-sulfur batteries assembled with carbonate electrolytes decays rapidly at 50°C. This is because carbonate electrolytes are prone to side reactions with metallic lithium at high temperatures. The use of polyionic liquid electrolytes to assemble lithium-sulfur batteries can avoid these problems and improve high-temperature cycle stability.
[0096] Example 9
[0097] The preparation method of the gel polymer electrolyte is as follows: 18.7g of lithium bis(fluoromethanesulfonyl)imide and 26g of methacryloyloxyethyl trimethylammonium chloride are dissolved in 10mL of deionized water, stirred with a magnetic stirrer for 10 minutes, the upper aqueous solution is removed, and 10mL of deionized water is added to wash the lower organic phase, and the process is repeated three times. After being frozen into a solid by liquid nitrogen, trace water is removed by freeze drying to obtain a polyionic liquid precursor monomer [MATAC] [FSI].
[0098] 0.4 g of polyionic liquid precursor monomer [MATAC][FSI], 0.374 g of lithium bis(fluoromethanesulfonyl)imide and 10 mg of azobis(isobutyronitrile) were dissolved in 1.6 g of 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide (Py 13 FSI) and stirred at room temperature for 1 hour. The solution was dripped onto the glass fiber diaphragm, and lithium foil, glass fiber diaphragm, lithium foil, steel sheet, and shrapnel were stacked on the 2032 button battery positive electrode shell in sequence, and finally covered with the 2032 button battery negative electrode shell. The sealing machine was pressurized and sealed, and the battery was placed in a glove box for 12 hours to ensure that the ionic liquid solution infiltrated the electrode surface. The button-type lithium-lithium symmetrical battery was taken out and placed in an oven and heated at 70 degrees Celsius for 12 hours. After heating, a lithium deposition-dissolution cycle test was performed at 50 degrees Celsius. Figure 4 As shown, under a current of 0.5 mA, a lithium deposition-dissolution cycle test was carried out, and the polarization voltage of the lithium-lithium symmetric battery was less than 25 mV. After 50 hours of cycling, the polarization voltage did not increase significantly, indicating that the polyionic liquid electrolyte has good stability to lithium metal.
[0099] Since the polyionic liquid electrolyte in the present invention can be applied to lithium ion batteries, the lithium salt used in the process of the present invention can be one or more of lithium salts used in the prior art (such as lithium difluorooxalatoborate, lithium bis(fluoromethylsulfonylimide), and lithium bis(trifluoromethylsulfonylimide).
[0100] Example 10
[0101] The preparation method is as follows: 30.1 g of lithium bis(trifluoromethanesulfonyl)imide and 26 g of methacryloyloxyethyl trimethylammonium chloride are dissolved in 10 mL of deionized water, stirred with a magnetic stirrer for 10 minutes, the upper aqueous solution is removed, and 10 mL of deionized water is added to wash the lower organic phase, and the process is repeated three times. After being frozen into a solid with liquid nitrogen, trace water is removed by freeze drying to obtain a polyionic liquid precursor monomer [MATAC] [TFSI].
[0102] 0.6 g of polyionic liquid precursor monomer [MATAC][TFSI], 0.574 g of lithium bis(trifluoromethanesulfonyl)imide and 40 mg of azobis(isobutyronitrile) were dissolved in 1.4 g of 1-methyl-1-propylpyrrolidinium bis(trifluorosulfonyl)imide (Py 13 TFSI) and stirred at room temperature for 1 hour. The solution was transferred to a glove box and dripped into a long polytetrafluoroethylene mold. The mold was sealed and heated at 70 degrees Celsius for 24 hours. The polyionic liquid electrolyte specimen was taken out of the mold for tensile testing. Figure 5 shown.
[0103] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essential content of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A polyionic liquid electrolyte for lithium-sulfur batteries, characterized in that: The polyionic liquid electrolyte for lithium-sulfur battery is obtained by heating a polyionic liquid precursor solution and then polymerizing it in situ; the polyionic liquid precursor solution comprises a pyrrolidine ionic liquid, a thermal initiator, a polyionic liquid precursor monomer and a lithium salt; The structural formula of the polyionic liquid precursor monomer is as follows: Wherein, X is one of bis(trifluoromethylsulfonyl)imide anion and bis(fluoromethylsulfonyl)imide anion; The pyrrolidine ionic liquid structural formula: Wherein, m is an integer of 1 to 2, and X is one of a bistrifluoromethylsulfonyl imide anion and a bisfluoromethylsulfonyl imide anion; The usage ratio of the polyionic liquid precursor monomer, the thermal initiator, the lithium salt, and the pyrrolidine ionic liquid is 0.25-0.67 g: 0.00625-0.00835 g: 1-4 mmol: 1 g; The positive electrode of the lithium-sulfur battery is a sulfur positive electrode, and the sulfur positive electrode is one of sulfurized polyacrylonitrile and sulfur-selenized polyacrylonitrile.
2. The polyionic liquid electrolyte for lithium-sulfur battery according to claim 1, characterized in that: The preparation method of the polyionic liquid precursor monomer is as follows: dissolving methacryloyloxyethyl trimethylammonium chloride and lithium salt in water, stirring for reaction, washing, and freeze-drying to obtain the polyionic liquid precursor monomer.
3. The polyionic liquid electrolyte for lithium-sulfur battery according to claim 1, characterized in that: The thermal initiator is one of azobisisobutyronitrile, azobisisoheptylnitrile and benzoyl peroxide; the lithium salt is one or more of lithium difluorooxalatoborate, lithium bistrifluoromethylsulfonyl imide and lithium bisfluoromethylsulfonyl imide.
4. A method for preparing a polyionic liquid electrolyte for a lithium-sulfur battery as claimed in claim 1, characterized in that: The preparation method comprises the following steps: A1, dissolving a polyionic liquid precursor monomer, a thermal initiator and a lithium salt in a pyrrolidine ionic liquid, and stirring to obtain a polyionic liquid precursor solution; A2. Under the protection of an inert atmosphere, the polyionic liquid precursor solution is heated to initiate an in-situ polymerization reaction of the polyionic liquid precursor monomer to obtain the polyionic liquid electrolyte for the lithium-sulfur battery.
5. The method for preparing a polyionic liquid electrolyte for a lithium-sulfur battery according to claim 4, characterized in that: In step A2, the heating temperature is 30 to 90° C., and the heating time is 5 to 600 minutes.
6. A lithium-sulfur battery comprising the polyionic liquid electrolyte according to claim 1.
7. A method for preparing a lithium-sulfur battery as claimed in claim 6, characterized in that: The preparation method comprises the following steps: dissolving a polyionic liquid precursor monomer, a thermal initiator and a lithium salt in a pyrrolidine ionic liquid, dripping the liquid onto a diaphragm, assembling a lithium-sulfur battery with a sulfur positive electrode and a lithium metal negative electrode on both sides, and initiating an in-situ polymerization reaction by heating to obtain a lithium-sulfur battery containing a polyionic liquid electrolyte.
8. The lithium-sulfur battery according to claim 6, characterized in that: The operating temperature range of the lithium-sulfur battery is 25°C-100°C.
Citation Information
Patent Citations
Ionic liquid polymer composite solid electrolyte and preparation method thereof, and lithium ion battery
CN108428931A